Effect of tillage system on epigeal and foliar insect predation in an organic cropping system in Pennsylvania, USA. - Shea A W Tillotson; Christina A Voortman; John M Wallace; Mary E Barbercheck (PLoS ONE)
Organic growers rely largely on cultural and biological control to manage pest populations and often use soil disturbance with inversion tillage to manage pests and weeds, incorporate crop residues and fertility amendments, and create seedbeds. Reduced-tillage systems are often associated with greater populations of insect generalist predators, as tillage can directly and indirectly disrupt predators and their activity. We investigated the in-season and legacy effects of soil disturbance in three organic feed grain and one forage production systems that varied in frequency and intensity of disturbance on epigeal predation rates on larval waxworms, Galleria mellonella L., and foliar predation rates on eggs of the western bean cutworm, Striacosta albicosta Smith, and European corn borer, Ostrinia nubilalis (Hübner), by arthropod natural enemies. The experimental site included three annual feed grain production systems comprised of a corn, Zea mays L., soybean, Glycine max (L.) Merr., and wheat Triticum aestivum L. sequence and one forage production system represented by a biculture of alfalfa, Medicago sativa L. and orchardgrass, Dactylis glomerata L. We also measured damage to corn ears from naturally occurring lepidopteran pests and corn yield. The epigeal predation rate on sentinel waxworms in the system managed predominantly with reduced tillage (64 ± 6.4%) was significantly greater than in the systems managed predominantly with inversion tillage (44 ± 5.5%) or with a shallow high-speed disk (48 ± 5.1%). There was no effect of intensity or frequency of soil disturbance on foliar predation or foliar predator community composition in corn. Damage to corn ears from lepidopteran pests was greater in the system managed predominantly with a shallow high-speed disk (51 ± 4.4% damaged ears) compared to systems predominantly managed with inversion tillage (35 ± 4.3%) or no-till planting (31 ± 1.4%). There was no difference in corn yield across systems, but corn yield variability was greatest in the reduced tillage system. We suggest that the occasional use of inversion tillage with a moldboard plow may not have lasting detrimental effects on foliar or epigeal predation rates on arthropod pests in annual organic grain production systems.